The Gendering of Farming : the Case of Norway - Haugen, Marit S. [Verfasser] (My University, 1998)
Based on a study of women farmers, the article raises the question how women can be seen as actors challenging the male dominance within agritulture. Wome-ns increased options to plan their own lives have also resulted in new approaches to farming. While the majority of older women adapted to gender expectations, mo:t younger women emphasized their occupational choice as farmers, indicating a rupture with gender expectations and traditions. The professional women farmers challenge and contest the vision of farmers as males. The changes we have seen in women-s farming roles coincide with what has happened within other sectors in Horway in the same period: more women have entered traditionally male positions. The work for greater equility between women and men has been part of profound political reform, where the changes in agriculture have started late, but are being put through as thoroughly as in other arenas of social life. (author's abstract, IAB-Doku) ((en)) Die norwegische Gleichstellungspolitik hat auch die berufliche Position von Frauen in der Landwirtschaft gestärkt. Eine Befragung von 84 Landwirtinennen zur Berufsrolle und zur beruflichen Identität in ihrem eher männlich geprägten Beruf zeigt, dass etwa die Hslfte eher traditionelle Einstellungen zu ihrer Arbeit hat, während eine Minderheit von jUngeren Landwirtinnen Uber ein professionelles Selbstverständnis verfUgt, dass nicht mehr mit der weiblichen Geschlechterrolle, wie sie den Frauen in bäuerlichen Betrieben zugeschrieben wird, konform geht. (IAB)
Keywords: S 6.1.1 Land-, Tier-, Forstwirtschaft und Gartenbau; G 2.4 Sozialer Wandel; P 1.3 Frauen; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.4 Biografiegestaltung; G 1.3.3.1 Qualifikationsverwertung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.3 Wandel von Arbeit & Wirtschaft; G 2.4.5 Gender Mainstreaming; I 2.2.1 Westeuropa; Landwirt; Erwerbstätige Frau; Berufsrolle; Berufsproblem; Frauen in Einzelberufen; Frauenarbeit; Berufliche Identität; Berufszufriedenheit; Männerberuf; Geschlechterrolle; Norwegen